Congenital Horner′s syndrome and the usefulness of the apraclonidine test in its diagnosis - Mirzai Hasan; Baser Esin (Indian Journal of Ophthalmology, 2006)
We present a seven-month-old baby with miosis of the left pupil, left hypochromia, mild ipsilateral ptosis, left hemifacial anhidrosis and asymmetrical facial flushing. A diagnosis of Horner′s syndrome (HS) was presumed and was confirmed by instillation of apraclonidine eye drops. Miosis was reversed upon apraclonidine instillation. Magnetic resonance imaging of the head, neck and thorax and ultrasonography of the neck and abdomen did not reveal any pathological conditions. Although delivery-related brachial plexus injury is known as the most common cause of congenital HS, it should be investigated and should include neuroimaging of the sympathetic pathway, to exclude a serious underlying disease. As in our case, a specific etiology may not always be elicited. Pharmacological testing with apraclonidine may be a practical alternative to cocaine in the diagnosis of HS.